Implementasi Etika Profesi Hukum untuk ASN di LLDIKTI - Hariyanto Huntua; Roy Marthen Moonti; Ibrahim Ahmad; Muslim A. Kasim (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Professional legal ethics plays a crucial role in carrying out the legal profession with integrity and fairness. For Civil Servants (ASN), especially those working at the Higher Education Service Institution (LLDIKTI), the implementation of professional legal ethics becomes even more critical, considering their role as bureaucrats who must uphold legal and ethical values in every decision they make. LLDIKTI is tasked with managing, supervising, and facilitating the organization of higher education in Indonesia, requiring its ASN to always adhere to principles of transparency, justice, and accountability in performing their duties. However, the implementation of professional legal ethics in LLDIKTI faces various challenges, including potential conflicts of interest, political pressure, complex bureaucracy, and limited human resources. This study aims to analyze the implementation of professional legal ethics in LLDIKTI and identify the challenges ASN face in applying these ethics. Additionally, the study seeks to provide recommendations on the steps that should be taken to optimize the implementation of professional legal ethics within the ASN environment in LLDIKTI. This research uses a qualitative approach, referring to legal ethics theories developed by Algra (2013) and Winarta (2007), as well as regulations governing ASN, such as Law No. 5 of 2014. The findings of this study are expected to contribute to the formulation of policies and training that enhance the professionalism and integrity of ASN in LLDIKTI.